PENGARUH UTANG TERHADAP PEREKONOMIAN NASIONAL (PERTUMBUHAN EKONOMI, KEMISKINAN, DAN PENGANGGURAN) - Dwi Resti Pratiwi; Dahiri (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2017)
Debt is the part of the government's fiscal policy which also being the part of the financial management policy. The financial management itself aims to improve people's welfare through the increase of economic growth, poverty reduction, and job creation. The purpose of this study is to analyse the impact of government debt on national economy including economic growth, proverty and unemployment rate. The study used data series of Indonesian economy including government debt, economic growth, poverty level and unemployment rate data from 2000 to 2016. The analytical method used was Granger causality and regression analysis. The result shows that there is a positive relationship between government debt and economic growth.